Factors Affecting the Participation of Iranian Elderly People in Sporting Activities from the Perspective of the Experts: A Qualitative Study - Hamid Sarani; Najaf Aghayi; Marjan Saffari; Hosein Akbari yazdi (Iranian Association of Health Education and Health Promotion, 2018)
Background and Objective: Aging is a sensitive period of human life and attention to the issues and needs of this era is a social necessity. Exercise is one of the issues that affects the elderly people's lives. Exercise plays an important role in the physical and mental health of elderly people. According to the importance of the subject, the aim of this study is identification of factors affecting the participation of Iranian elderly people in sporting activities Methods: The statistical population of the study is experts in the field of ageing sports. The sampling was done purposefully. The data collection tool was a semi-structured interview. After 14 interviews the researcher reached a theoretical saturation. The collected data, was analyzed using qualitative content analysis method.            Results: 2 themes and 12 subthemes were emerged from data analysis that included individual factors (8 subthemes) and organizational factors (four subthemes). These themes were separated into 12 subthemes: social motives, physical fitness motives, medical motives, agent of pleasure and relaxation, receiving incentives, elderly people's knowledge, needs of elderly people, promotional methods, organizational policies, places and facilities and sports programs. Conclusion: According to research findings, it is suggested to managers that planning for the participation of the elderly people in sporting activities must be considered along with the motivation for participation, individual factors and organizational factors, in order to be more effective.